Análise da política de incentivos fiscais da Prefeitura Municipal de Fortaleza e seus efeitos no mercado de trabalho - Meneses, Mayara Ellen de Vasconcelos (2024)
The granting of tax incentives consists of an economic policy that aims to develop economic activity in each sector and region, with the aim of promoting economic growth in less developed regions, through the reduction and/or elimination of company taxes. In view of this, this dissertation analyzes some tax incentive policies of the Municipality of Fortaleza, through the Programs of the Municipal Secretariat for Economic Development. Taken together, the results point to the fact that economic sectors present distinct characteristics in terms of employment, age of workers, average income, and accumulated experience and that, despite variations between sectors, the general average number of employment relationships is significant, reflecting a substantial contribution to the generation of income and employment. Furthermore, average income remains below ideal, requiring attention to ensure equal pay and quality of life for workers.